1998
DOI: 10.1300/j021v19n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Alumni Perspectives of a Graduate Certificate in Gerontology Program

Abstract: Gerontological educators have had a long-standing interest in student outcomes, surveying alumni of educational programs about the usefulness of their training for aging-related employment. This article describes a study of Graduate Certificate in Gerontology alumni from Virginia Polytechnic Institute and State University. A survey found that graduates reported their certificate training in gerontology was useful, but would have liked more training in practical and applied aspects of working on behalf of older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The main instrument used to collect data was a self-administered questionnaire, which was developed based on the concepts of practice competencies and the question styles used in previous studies (Bennett & Sneed, 1999;Henderson et al, 1998;Roberto et al, 1997;Usita et al, 1998), and on the feedback of nine alumni who represented the fields of medicine, nursing, and social work. The finalized questionnaire contained six sections including sociodemographic background, education and training, current employment, perceived importance of practice competency, perceived adequacy of training, and suggestions for improvement.…”
Section: Methodsmentioning
confidence: 99%
“…The main instrument used to collect data was a self-administered questionnaire, which was developed based on the concepts of practice competencies and the question styles used in previous studies (Bennett & Sneed, 1999;Henderson et al, 1998;Roberto et al, 1997;Usita et al, 1998), and on the feedback of nine alumni who represented the fields of medicine, nursing, and social work. The finalized questionnaire contained six sections including sociodemographic background, education and training, current employment, perceived importance of practice competency, perceived adequacy of training, and suggestions for improvement.…”
Section: Methodsmentioning
confidence: 99%
“…The alumni of gerontology programs want to acquire more knowledge and skills in management, communication, policy issues, and various dimensions of the aging process (Association for Gerontology in High Education, 1994;Peterson, 1995;Usita, Blisezner, & Roberto, 1998). They consider interdisciplinarity, multidisciplinary opportunities for learning, and practicum experience to be the most valuable components of a gerontology program (Euster & Reaves, 1995;Usita et al, 1998).…”
Section: Gerontology and Geriatrics Educationmentioning
confidence: 99%
“…Numerous studies have confirmed that a majority of graduates are able to secure aging-related employment after completing their gerontological studies (Euster & Reaves, 1995;Filinson, 1993;Roberto et al, 1997;Usita et al, 1998). Students with prior experience in gerontology and geriatrics work have been found to fare better in securing aging-related employment after certificate completion than their less experienced counterparts (Rueb, Weber, & Hesser, 1994).…”
mentioning
confidence: 97%
“…Because of the varied needs of older adults, students interested in teaching, administration, planning, advocacy, research, and direct services can benefit from the specialized preparation of a certificate program. The development of marketable skills and knowledge along with practical assistance with job placement are reported benefits of a gerontology credential (Roberto et al, 1997;Usita et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation